FORMS AND METHODS OF TEACHING DISCIPLINE ``ECOLOGICAL EXPERTISE'' FOR STUDENTS ECOLOGISTS - RIDEI, Nataliia; PALAMARCHUK, Svetlana (Trends in education, 2012)
The article deals with the forms and methods, the analysis of the content of the subject ``Environmental assessment'' for student environmentalists highlighted the main criteria of knowledge and skills in the study of the course. Submitted characteristics and structure of discipline and learning activities.
Keywords: ecological expertise; skill analysis; the structure of discipline; training activities.